Literature and Propaganda: The Structure of Conversion in Schenzinger's Hitlerjunge Quex - John Daniel Stahl (Studies in 20th & 21st Century Literature, 1988)
Propaganda literature as a genre can profitably be analyzed by means of a structuralist approach, as Susan R. Suleiman has shown in her study of the French ideological novel. Extending her discussion of the "structure of confrontation" and the "structure of apprenticeship," this study postulates the "structure of conversion" as a fundamental form of propaganda literature. Through loss of self to a greater entity, the central character in fiction exemplifying this form finds a new identity in self-submergence. A once-popular novel by the German pro-fascist author Karl Aloys Schenzinger, Hitlerjunge Quex ( 1932), serves as a model for investigation into the structure of conversion. Religious and psychological dimensions of the central character's experience merge in a representation of conversion that is all the more powerfully ideological for disguising its political and racial assumptions. Eros and Thanatos meet in the mythic heightening of self-sacrifice, culminating in martyrdom. A consideration often ignored by structuralist critics, the use of stylistic means to reinforce implied messages, is shown to be a significant element in Hitlerjunge Quex. The value of a structuralist approach to propaganda lies in its elucidation of hidden assumptions, exposing them to critical judgment.
Keywords: Propaganda literature; structuralist approach; Susan R. Suleiman; French ideological novel; structure of confrontation; structure of apprenticeship; structure of conversion; loss of self; German; pro-fascist; Karl Aloys Schenzinger; Hitlerjunge Quex; Religious; psychological; political; racial; conversation; Eros; Thanatos; self-sacrifice; martyrdom